Síntese de compostos contendo núcleos de pirimidínicos derivados de β-enaminodicetonas - Andrade, Valquiria Pereira de (2019)
In this work the reactivity of β-enaminodiketones [RC(O)C(=CHNMe2)C(O)R1], (wher R= C6H5, 4-Me-C6H4, 4-OMe-C6H4, 4-Cl-C6H4 4-NO2-C6H4, thien-2-yl and furan-2-yl) and R1 (CF3 and CO2Et), was studied with dinucleophiles such as: N-substituted 2-methylisothiourea sulfates, 3-amino-1H-(1,2,4)-triazoles, and 2-aminobenzimidazole. The novel 5-trifluoromethyl[1,2,4]triazolo[1,5-a]pyrimidines were obtained in a highly regioselective manner from the cyclocondensation reaction between β-enaminodike-tones and 3-amino-triazoles in good yields. (72-90%). Then, the β-enaminodiketones were cyclocondensed with different 2-methylisothiurea sulfates, with the general for-mula [R1NHC(SMe)NH]2.H2SO4 where (R1= Me, Et, Ally). The pyrimidines were obtai-ned with high regioselectivity, and good yield (81-95%), when the reaction was perfor-med in basic medium using chloroform as the solvent. In this same reaction when the solvent was changed to acetonitrile, the elimination of the CF3 group occurred, thus obtaining the pyrimidinones in good yields (65-87%). Dihydrobenzo[4,5]imido[1,2-a]pyrimidines were selectively obtained through the reaction of β-enaminodecetones with 2-aminobenzimidazole, furnishing the expected products in good yields (87-98%), Finally, Benzo[4,5]imido [1,2-a]pyrimidines carboxylates were obtained in high purity and excellent yields (90 to 97%). The novel heterocycles obtained in this work were characterized by Hydrogen and Carbon Nuclear Magnetic Resonance, HMBC two-di-mensional NMR, Mass Spectrometry, Elemental Analysis and X-ray Diffraction.